Phenomenological Insights into Arabic Language Learning under Indonesia’s Merdeka Curriculum - Ahmad Rizki Nugrahawan Rizki; Miatin Rachmawati; Zahra Maulida Fitri; Rahmatika Dewi (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2025)
The purpose of this study is to explore the phenomenological impacts experienced by teachers and students in the implementation of Arabic language learning under the Merdeka Curriculum at MAN 4 Jakarta. Using a phenomenological approach, this research examines teaching practices and instructional materials from both teachers’ and students’ perspectives. The findings indicate positive impacts on students’ Arabic learning, reflected in improved academic achievement, learning progress, and success, including accomplishments in Arabic Language Olympiad competitions resulting from differentiated learning practices. Teachers also benefit from the curriculum’s conceptual and flexible teaching materials, which enable them to design and develop personalized instructional resources. Overall, the Merdeka Curriculum promotes student-centered learning, enhances instructional creativity, and fosters meaningful learning experiences in Arabic language education.